Eradication therapy for gastric cancer in Inner Mongolia: a single-center study over 10 years - Ya-Hong Li; Ming Liu; Xue-Yu Zhao; Fei Song; Dong-hai Li (Journal of the Pakistan Medical Association, 2021)
Objective: To analyze the clinicopathological data of gastric cancer database in The Affiliated Hospital of Inner Mongolia Medical University for the past 10 years, in order to understand the characteristics, diagnosis and treatment of gastric cancer in this area. Methods: The clinical and pathological data of 2049 patients with gastric cancer treated in the Affiliated Hospital of Inner Mongolia Medical University from 2007.1-2017.1 were retrospectively analyzed. All clinical data in the present study were approved by the Ethics Committee of Inner Mongolia Medical University. The efforts were made to keep patient information used in the studies. Results: There were 1619 males (79.01%) and 430 females (20.99%) with an average age of 60.94±10.90. The incidence of gastric antrum was the highest in 830 cases (40.51%) and the proportion of gastric cancer was different in different age groups (c2=58.583, P=0.000). Early stage gastric cancer accounted for 8.83%, while advanced gastric cancer accounted for 91.17%. 922 cases (45.00%) were poorly differentiated adenocarcinoma. There were significant differences in the histological types of gastric cancer among different age groups (c2 = 102.866, P = 0.000). There were 130 cases of Mongolian patients with gastric cancer, and the composition ratio of each age group was similar to that of Han ethnicity. However, incidence location was different from that of the Han ethnicity, 55 cases (42.31%) occurred in esophagogastric junction, followed by gastric antrum. Continuous....